Membrane Bioreactor for Pharmaceuticals and Personal Care Products Removal From Wastewater - Hena, S.; Znad, Hussein (2018)
© 2018 Elsevier B.V. This chapter discusses about the emerging micropollutants mainly focusing on pharmaceuticals and personal care products (PPCPs). The chapter also covered some aspect of conventional process of removing micropollutants commonly referred as conventional activated sludge; however, more detail is available on membrane bioreactor (MBR), its mechanisms, and factors effecting PPCPs removal. It has also been discussed how sludge system improves the efficiency of MBR in term of PPCPs removal. A brief discussion is made on advantages and limitation of MBR. However, hybrid MBR technologies are discussed here to resolve some limitations of MBR. Simultaneously, the potential impacts of a number of operational hazardous proceedings on MBR are discussed to facilitate how to improve environmental and human health risk management.